Pemberian Unsur Hara Fermentasi Dari Limbah Cangkang Telur Ayam Terhadap Pertumbuhan Tanaman Cabai Merah (Capsicum annum L.) - Putri Tunggal Dewi, Citra; Novianti, Dewi; Panca Putri, Yunita; Anggraini, Putri (Indobiosains, 2024)
Research on the provision of fermented nutrients from chicken eggshell waste on the growth of red chili (Capsicum annum L.) aims to analyze the concentration of chicken eggshell nutrients that have the best effect on the growth of red chili (Capsicum annum L.). The research was carried out from April 2023 to June 2023 at the Biology Green House, Faculty of Science and Technology, PGRI Palembang University. Using the experimental method Completely Randomized Design (CRD), with 5 treatments namely P0 (control), P1 (100ml/L water), P2 (150ml/L water), P3 (200ml/L water), and P4 (250ml/L water) ), The treatment was repeated 4 times and the results showed that the best concentration was in the P4 treatment with a dose (250 ml/L of water) for plant height (14.87), number of leaves (12) and stem diameter (0.65).